P075: Targeted temperature management was associated with worse outcomes of non-shockable out of hospital cardiac arrest. (May 2020) - Kawano, T.; Grunau, B.; Scheuermeyer, F.; Fordyce, C.; Stenstrom, R.; Christenson, J.
Abstract : Introduction: We sought to assess the effect of in-hospital targeted temperature management (TTM) on outcomes of non-shockable out-of-hospital cardiac arrest (OHCA). Methods: This is a secondary analysis of a randomized controlled trial "A Randomized Trial of Continuous Versus Interrupted Chest Compressions in Out-of-Hospital Cardiac Arrest" (NCT01372748). We included non-traumatic comatose OHCAs with non-shockable rhythm who survived to hospital admission. Outcomes of interest were survival at hospital discharge and favorable neurological outcome (modified Rankin scale 0-3). We performed multivariable logistic regression, adjusting for baseline characteristics to determine the association between TTM and outcomes, compared to no TTM, for the entire cohort as well as for the propensity matched cohort. Results: Of 1, 985 OHCAs who survived to hospital admission, 780 (39.3%) were managed with TTM. In TTM patients, 7.3 % patients survived to hospital discharge and 3.9 % had a favorable neurological outcome in contrast to 10.2 % and 6.1 %, respectively, in no TTM patients. Multivariable analyses demonstrated an association between TTM and decreased probability of both outcomes, compared to no TTM (adjusted ORs for survival: 0.67 95% CI 0.48–0.93, and for favorable neurological outcome: 0.57 95% CI 0.37–0.90). Propensity score matched analyses demonstrate the similar results. Conclusion: TTM might decrease the probability of neurologically intact survival for non-shockable OHCAs.